Nearest points on toric varieties - Helmer, Martin; Sturmfels, Bernd (MATHEMATICA SCANDINAVICA, 2018)
We determine the Euclidean distance degree of a projective toric variety. This extends the formula of Matsui and Takeuchi for the degree of the A-discriminant in terms of Euler obstructions. Our primary goal is the development of reliable algorithmic tools for computing the points on a real toric variety that are closest to a given data point.